Influence of polyfunctional nanomodificators on the microstructure of concrete composites of high strength and density - Sumariuk, O. V.; Romankevych , V. F.; Halunka , O. D.; Kutsyk, O. V.; Polevetsky, V. V.; Novikov, S. M.; Fodchuk , I. M. (Physics and Chemistry of Solid State, 2020)
The patterns of formation of highly functional concretes structure, which consist in formation of an ordered, low-porous, fine-crystalline microstructure of cementitious matrix, in particular due to pozzolanic reactions of the non-clinker part of the binder with formation of an additional amount of low-basic hydrocarbons, are investigated.